GABAergic gene expression in postmortem hippocampus from alcoholics and cocaine addicts; corresponding findings in alcohol-naïve P and NP rats. - Mary-Anne Enoch; Zhifeng Zhou; Mitsuru Kimura; Deborah C Mash; Qiaoping Yuan; David Goldman (PLoS ONE)
Background By performing identical studies in humans and rats, we attempted to distinguish vulnerability factors for addiction from neurobiological effects of chronic drug exposure. We focused on the GABAergic system within the hippocampus, a brain region that is a constituent of the memory/conditioning neuronal circuitry of addiction that is considered to be important in drug reinforcement behaviors in animals and craving and relapse in humans. Methodology Using RNA-Seq we quantified mRNA transcripts in postmortem total hippocampus from alcoholics, cocaine addicts and controls and also from alcohol-naïve, alcohol preferring (P) and non-preferring (NP) rats selectively bred for extremes of alcohol-seeking behavior that also show a general addictive tendency. A pathway-targeted analysis of 25 GABAergic genes encoding proteins implicated in GABA synthesis, metabolism, synaptic transmission and re-uptake was undertaken. Principal findings Directionally consistent and biologically plausible overlapping and specific changes were detected: 14/25 of the human genes and 12/25 of the rat genes showed nominally significant differences in gene expression (global p values: 9×10⁻¹⁴, 7×10⁻¹¹ respectively). Principal FDR-corrected findings were that GABBR1 was down-regulated in alcoholics, cocaine addicts and P rats with congruent findings in NSF, implicated in GABAB signaling efficacy, potentially resulting in increased synaptic GABA. GABRG2, encoding the gamma2 subunit required for postsynaptic clustering of GABAA receptors together with GPHN, encoding the associated scaffolding protein gephryin, were both down-regulated in alcoholics and cocaine addicts but were both up-regulated in P rats. There were also expression changes specific to cocaine addicts (GAD1, GAD2), alcoholics (GABRA2) and P rats (ABAT, GABRG3). Conclusions/significance Our study confirms the involvement of the GABAergic system in alcoholism but also reveals a hippocampal GABA input in cocaine addiction. Congruent findings in human addicts and P rats provide clues to predisposing factors for alcohol and drug addiction. Finally, the results of this study have therapeutic implications.